Manon Lescaut: Geschichte einer Leidenschaftlichen Liebe - Prévost Abbé 1697-1763; Haemmerling, Konrad 1888-1957 (Munich Goldmann, 1958)
The story, set in France and Louisiana in the early 18th century, follows the hero, the Chevalier des Grieux, and his lover, Manon Lescaut. Controversial in its time, the work was banned in France upon publication. Despite this, it became very popular and pirated editions were widely distributed. In a subsequent 1753 edition, the Abbé Prévost toned down some scandalous details and injected more moralizing disclaimers. The work was to become the most reprinted book in French Literature, with over 250 editions published between 1731 and 1981.
'Histoire du Chevalier des Grieux, et de Manon Lescaut' is a novel by Antoine François Prévost. Published in 1731, it is the seventh and final volume of 'Mémoires et aventures d'un homme de qualité'.
Originally published in 1731
Keywords: 18th Century (1701-1800); 20th Century (1901-2000); Novel; France